PENGARUH KUALITAS PRODUK WISATA DAN HARGA TIKET TERHADAP KEPUASAN PENGUNJUNG KAMPUNG MAIN CIPULIR - Rozi Yuliani (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
Tourism object that are able to compete in the markets are the company that providesquality products or services and ticket price that suitable with tourist expectation. Sothe tourism object is expected to continue to make improvements, especially on qualityof products, services and price. Tourism object also need to seek advice service to givethe best to their tourist. This requires the identification of the main determinants ofproduct quality and price from the perspective of the tourist.This study aims to determine the influence of quality tourism product and ticket priceon tourist satisfaction. Where is the independent variable consist of quality tourismproduct and ticket price influence’s tourist satisfaction variable as the dependenvariable, either partially or simultaneously.The research methode used is quantitative methode with explanatory survey approach,the research done on large and small populations studied, but the data is the dataobtaine from samples taken from the population by using statistical methods, while thestatistical methods used in data analysis in multiple linier regression.The results showed that the first hypothesis is partially the quality tourism product hassignificant influence on tourist satisfaction. The second hypothesis of the test resultsshowed that partially, the ticket price has significant influence on tourist satisfaction.And the third hypothesis showed that simultaneous the quality tourism product andticket price has significant influence on tourist satisfaction.Conclusions from the research is that the three hypothesis proposed research isacceptable, that is there are significant influences the quality tourism product an ticketprice to tourist satisfaction either partially or simultaneously. Advice from the author is to increase tourist satisfaction can be done by the way to repair the ticket price suitablewith visitor capability